Perceptions, attitudes, behaviours and barriers towards obesity among people with obesity and health care professionals in Indonesia: An exploratory online survey - Sidartawan Soegondo; Gaga Irawan Nugraha; Farid Kurniawan; Ana Asmara Jannati; Dicky L. Tahapary (PLoS ONE, 2026)
Background The Awareness, Care, and Treatment In Obesity maNagement Asia Pacific (ACTION APAC) online survey identified perceptions, attitudes, and barriers to effective obesity care among People with Obesity (PwO) and Health Care Professionals (HCP) across nine APAC countries. Here, we present findings from Indonesia. Methods This was a cross-sectional, observational, descriptive survey in PwO (≥18-year-old) with self-reported body mass index of ≥25 kg/m 2 and HCPs who spent ≥50% of their time in direct patient care. The survey was conducted between 20 April, 2022 to 11 May, 2022. The questionnaires were approved by the institutional review board as per local regulations. Findings A total of 1,000 PwO and 200 HCPs completed the survey. Notable differences were observed among PwO and HCPs in acknowledging obesity as a chronic disease (54% PwO and 90% HCPs), considering weight loss as PwO responsibility (91% PwO and 17% HCPs) and in agreeing that PwO were motivated to lose weight (76% PwO and 50% HCPs). Almost, two-thirds (67%) of PwO perceived themselves as either overweight or normal weight while only 30% discussed weight with their HCPs in the past five years. Financial concerns (45%) and assuming self-responsibility for weight loss (43%) were cited as the top reasons for not discussing. Only 53% HCPs initiated weight conversations, as they believed that PwO were either not motivated (55%) or not able to lose weight (51%). When discussed, most (68%) HCPs recommended lifestyle changes. Interpretation Our study identified gaps in understanding obesity as a disease and its management among PwO and HCPs, highlighting a need for increased awareness to improve obesity care in Indonesia.